Quality of life of patients undergoing surgery for obstructed defecation syndrome: A before-after study. (September 2015) - Racaniello, Emanuela; Terzoni, Stefano; Accardi, Roberto; Ricci, Cristian; Boccasanta, Paolo; Destrebecq, Anne
Abstract: Introduction: Obstructed defecation syndrome (ODS) is the inability to evacuate the contents of the rectum. It is a common problem with both social and psychological effects on a patient's quality of life. Surgery has proven effective and safe in reducing symptoms, with subsequent improvement of quality of life (QOL). Methods: This study evaluates QOL both before and after surgery (three months) in a series of 96 patients. The Short Form-12 (SF-12) and ODS questionnaires were scored and pain during voiding was assessed by means of the Numerical Rating Scale. Results: 92 consecutive patients were studied. After three months, pain and ODS scores improved significantly. General QOL also improved significantly. Discussion: More than three months from surgery might be necessary in order to obtain more useful information regarding the effects of surgery on both physical and mental health. However this study suggests the benefits are seen even in the early post-operative period. Conclusion: After three months general quality of life shows a improvement and hopefully these results will be sustained (or even improved) in the longer term. Highlights: What is already known on this topic? Obstructed defecation syndrome is a very common problem and deeply affecting quality of life. What this study adds? In our sample, surgery led to ODS symptoms relief after 3 months.